ArcGIS story maps in improving teachers’ Geography awareness - Purwanto Purwanto; Ike Sari Astuti; Rudi Hartono; Ghada Abd Elsattar Mohammed Oraby (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2022)
The purpose of this study is to examine the use of story maps in increasing sustainable Geography awareness among Geography teachers. The advent of story maps has altered the current Geography education in the digital era. ArcGIS story maps are a type of user-friendly geospatial technology renewal. This story map is believed capable of helping students learn Geography more independently, transforming Geography education. This belief should be reinforced by implementing story maps on their own Geography teachers, who have low Geography literacy rates in general. This action research involved 67 Geography teachers who were members of the East Java Geography Teacher Working Group, with various backgrounds, ages, and teaching experiences. Learning is implemented using blended learning and the in-on-in model. With blended project-based learning, this research was conducted to solve problems related to high school teachers' low Geography awareness. To identify the effects of the treatment, the obtained data were analyzed using a different test with paired t-test. The findings showed that story maps could increase long-term geographic awareness, illustrated by the obtained significant level of more than 0.05. This success is influenced by teachers' knowledge and experience with geospatial technology, as well as their age. Although the ability to create story projects is limited, the use of story maps provides a meaningful experience for teachers to think, reason, and act geographically.